Her own person: Gender, youth and citizenship - Garcia, Loreley Gomes; da Silva, Marina Blank Virgilio (Seven Editora, 2023)
This article crosses gender and citizenship, addressing empowerment, feminism, violence and the notion of equality. Methodologically, we used interviews and self-defense workshops for women, approaching these themes with adolescents and young women participating in actions by partner NGOs that develop empowerment actions for young women. We propose to detect attitudes that involve the girls' agency and the perceptions they have about the themes, in addition to other important notions for the research, such as sexuality, femininity, leadership and life projects. We seek to understand the impacts of the projects in which these young people participate in their perception of these experiences and how the stimulus for individual and collective actions is given.The main objective is to analyze the connection between agency, implemented in practice, and citizenship. If the young women understand and act within the scope of the search for equality and rights, there will be speeches and actions that give clues about how this works, an exercise of decision and action on issues that go beyond the private sphere. Young women negotiate new discourses about femininity and gender equality while making decisions that affect themselves and others in social interactions, a personal and cultural construct. This conception will have a direct impact on the construction of the young woman's citizenship, which will also show several traces of incompleteness. We understand that when investigating the practices and performances that constitute 'girlhood', we can perceive young women as transforming social agents, whether in the choice of sociocultural discourses that will build on gender, whether in assertiveness in their projects or participation in the public space triggering empowerment.DOI:https://doi.org/10.56238/alookdevelopv1-089